Life 101: Time Management: These two time management strategies are easy for college students to use and can generate big payoffs. Issue 3 (February 2015) - McCune, Michael
Colleges offer many activities for students, and some students have trouble managing their time to fit everything in. The author, a recent college graduate, offers two time management strategies: study in between classes and be present in the moment.